Finite Element Based Dynamic Characteristics of Journal Bearing in a New Two-Stroke Linear Generator Engine - M.M, Rahman; A.K, Ariffin (Malaysian Journal of Science, 2006)
This paper presents the dynamic characteristics of hydrodynamic journal bearing in a new two-stroke linear generator engine to solve tribological problems considering constant viscosity of the lubrication using the finite element method. The tribological phenomenon of the sliding surfaces between connecting rod and bush may be among the most complex in the linear generator engine and could become even more severe with increasing the engine power. The friction between the connecting rod and bush significantly contributes to the power losses of the engine. On the basis of the finite element analysis theory, the Reynolds equation for dynamic loads is derived. The results represent the bearing characteristics, namely the variation of pressure along the circumference, effects of load-carrying capacity, frictional losses, and stiffness and damping coefficient with the eccentricity ratio and also presented the variation of eccentricity ratio with Sommerfeld number. Results from the numerical analysis indicated that the effect of load-carrying capacity, frictional losses strongly depends on the eccentricity ratio. It also shows that the dynamic characteristics, namely stiffness and damping coefficients also greatly depends upon the eccentricity ratio. This paper also investigated the performance characteristics of the journal bearing as well as on its stability.